Pengaruh Pendidikan Kesehatan Menggunakan Leaflet Berbahasa Daerah terhadap Tingkat Pengetahuan Penderita Hipertensi di Desa Lambanan Kabupaten Mamasa - Nurfadhila, Nurfadhila; Wahab, Masyitah; Mae, Mae (LPPM Hang Tuah Pekanbaru, 2024)
Health education is part of health efforts aimed at improving lifestyle and providing knowledge, especially about the dangers of hypertension and how to prevent it The aim of the research was to determine the effect of health education using regional language leaflets on the level of knowledge of hypertension sufferers in Lambanan Village, Mamasa Regency. The design in this research is quasi-experimental, with a one-group pre-post test research design and a sample size of 31 people. Data was collected using a culturally adapted hypertension education questionnaire (CAHE) for 2 weeks in August 2024. This study showed the pre-test group with an average score of 6.42 and the post-test group with an average score of 9.48. The conclusion is that the results of this study show that the p-value is 0.000>0.005 and that health education using regional language leaflets can be an alternative for increasing the knowledge of hypertension sufferers.